Pulmonary CXCR2 regulates VCAM-1 and antigen-induced recruitment of mast cell progenitors - Hallgren, Jenny (National Academy of Sciences, 2007)
Chemokine receptors regulate the trafficking of leukocytes by mediating chemotaxis and by their influence on the expression and/or affinity of leukocyte integrins. Using blocking mAb, we showed that antigen-induced recruitment of mast cell progenitors (MCp) to the lung requires interaction of a4 integrins on the MCp with endothelial vascular cell adhesion molecule 1 (VCAM-1). In seeking a chemokine component, we found that CXCR2-deficient but not CCR3- or CCR5-deficient sensitized and antigen-challenged mice have significantly fewer lung MCp 1 day after challenge and fewer tracheal intraepithelial MC 1 week after challenge, implying that recruited MCp provide the source for these mature MC. Unexpectedly, reconstitution of sensitized, sublethally irradiated +/+ and −/− mice with bone marrow cells of either genotype indicated that expression of CXCR2 by the migrating MCp was not required. Instead, receptor function by resident lung cells was required because normal BM did not reconstitute MCp recruitment in irradiated CXCR2(−/−) mice. The reduced MCp influx into the lung of CXCR2(−/−) mice was accompanied by reduced induction of VCAM-1 transcripts and reduced endothelial surface expression. Thus, these studies demonstrate a role for a chemokine receptor in regulating endothelial VCAM-1 expression, MCp migration, and the level of intraepithelial MC in the lung of aerosolized, antigen-challenged mice.